Assessment of Nurses Knowledge and Practice Regarding Pharmacology of the Drugs They Usually Used in Tertiary Hospital - Mohammed Dafer Misfer Alalhareth; Ebrahim Nasser Mosfer Alalhareth; Saleh Nasser Mosfer Alalhareth; Misfer Dafer Misfer Alalhareth; Saeed Misfer Dafer Al Alhareth; Mohammad Nasser Mosfer Al Alhareth; Mohammed Saeed Ali Alalhareth; Mahdi Shaya Amer Al Shurayyan (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Medication safety is a critical aspect of patient care, with nurses playing a central role in ensuring safe medication administration. Despite global initiatives such as the World Health Organization’s Medication Without Harm campaign, medication errors remain prevalent in healthcare systems. These errors, particularly in the medication administration process, are often linked to gaps in nurses’ knowledge, attitudes, and practices. This study aims to assess nurses knowledge and practice regarding pharmacology of the drugs they usually used in tertiary hospital. Methods: A descriptive correlational cross-sectional research design was employed to explore the relationships between nurses’ knowledge, attitudes, and practices in medication administration. A sample of 140 nurses was selected using simple random sampling from a population of 700 nurses. Data were collected using two main tools: a knowledge and attitude questionnaire and a performance checklist. Descriptive statistics, Pearson’s correlation, and Chi-square tests were used to analyze the data. Results: The majority of nurses (97.9%) were female, and 98.6% reported no formal training in medication administration. Knowledge scores were generally low, with 62.9% of nurses demonstrating insufficient understanding of medication administration. Attitudes toward medication administration were evenly split, with 51.4% expressing positive attitudes. Practices in medication administration were suboptimal, with over 75% of nurses demonstrating poor preparation practices and around 60% displaying inadequate administration practices. Significant positive correlations were found between nurses’ knowledge, attitudes, and practices (p ≤ 0.05). Conclusion: This study highlights critical gaps in nurses’ knowledge, attitudes, and practices regarding medication administration, which could potentially lead to medication errors. The findings underscore the need for targeted training programs to improve nurses’ competency in medication administration and reinforce positive attitudes towards patient safety. Further research is needed to assess the effectiveness of such interventions and to explore the impact of socio-demographic factors on nursing practices in medication administration.